The Importance of E-Textbooks in Teaching Computer Graphics - R.R. Umirzaqov; R M. Mambetov; M.U. Nosirov (Genius Publishing Group, 2022)
This article discusses the importance of using an electronic textbook in teaching Computer Graphics. The article describes the possibilities of e-textbooks.
Keywords: Electronic Textbook; Graphics; Algorithms; Resource